Monocyte/HDL ratio in sarcoidosis patients without treatment (Annals of Medical Research, 2021)
Aim: This study examined the effects of monocyte/high-density lipoprotein cholesterol (HDL-C) ratio (MHR) and other inflammatory markers in patients with sarcoidosis not receiving treatment. To our knowledge, this is the first study on the relationship between sarcoidosis and MHR.Material and Methods: This study included 53 patients with sarcoidosis who were followed at a single, outpatient tertiary-care centre. Data on patient demographics (age and gender), disease characteristics (duration of disease, radiographic stage, treatments); pulmonary function tests (% predicted values for forced vital capacity [FVC], forced expiratory volume at 1 second [FEV1], diffusing capacity of the lungs for carbon monoxide [DLCO], alveolar volume [VA], forced expiratory flow [25–75% and at 50%; FEF] [FEF25-75]), blood biochemistry and hemogram findings were retrieved from hospital records.Results: Mean ± SD patient age was 51.13 ±1 1.94 years. Of the 53 patients, 42 were female and 11 were male. When compared with MHR ratio and pulmonary function test parameters, there was a negative correlation with FEV1% (P = 0.043, r = −0.279) and DLCO% (P = 0.009, r = –0.360). There was no significant correlation between FVC, FEV25-75 or VA. No significant correlation was found between blood calcium, urinary calcium, SACE (serum angiotensin converting enzyme) values and MHO ratio.Conclusions: Large-scale prospective studies are needed to determine if the use of MHR as an indicator of inflammation and activation would be helpful in the diagnosis and monitoring of patients with sarcoidosis.